Ice nucleation, shape, and composition of aerosol particles in one of the most polluted cities in the world: Ulaanbaatar, Mongolia. (August 2016) - Hasenkopf, Christa A.; Veghte, Daniel P.; Schill, Gregory P.; Lodoysamba, Sereeter; Freedman, Miriam Arak; Tolbert, Margaret A.
Abstract: Air pollution is attributable to 7 million deaths per year, or one out of every eight deaths globally. In particular, high concentrations of particulate matter (PM), a major air pollutant, have significant impacts on health and regional climate in urban centers. Many of the most polluted places, largely in developing countries, go severely understudied. Additionally, high particulate matter levels can have an impact on the microphysical properties of clouds, impacting precipitation and regional climate. Semi-arid regions can be especially affected by small changes in precipitation. Here we characterize the physical and chemical properties of PM in one of the most PM-polluted cities in the world: Ulaanbaatar, Mongolia, a semi-arid region in central Asia. Twice monthly aerosol samples were collected over 10 months from a central location and analyzed for composition and ice nucleation activity. Almost all particles collected were inhalable, consisting primarily of mineral dust, soot, and sulfate-organic. In winter, all classes of PM increase in concentration, with increased sulfur concentrations, and the particles are less active towards heterogeneous ice nucleation. In addition, concurrent monthly average PM10, SO2, NOx, and O3 levels and meteorological data at a nearby location are reported and made publicly available. These measurements provide an unprecedented seasonal characterization of the size, shape, chemical structure, and ice nucleating activity of PM data from Ulaanbaatar. This 10-month field study, exploring a variety of aerosol properties in Ulaanbaatar, Mongolia, is one of very few such studies conducted in the region or in such a highly polluted environment. The results of this study may inform work done in other similarly situated and polluted cities in Asia and elsewhere. Graphical abstract: Highlights: Ulaanbaatar, Mongolia has the second highest PM10 concentrations globally. Almost all particles are inhalable, composed of minerals, soot, and sulfate-organic. Particle concentration and sulfur content of particles increases in winter. Particles collected in winter have lower ice nucleation activity.